Analysis of Factors Influencing Consumer Behavior Bring Their Own Shopping Bag (Case Study KecamatanTembalang) - Aries Susanty; Dyah Ika Rinawati; Fairuz Zakiah (Bandar Lampung University (UBL), 2012)
People can start with